Comparative Clinical Study of Role of Saraswatchurna in Apasmar - Sonali Dilip Wairagade1 , Tanvi Wairagade2 , Anuja Vasant Nagrare3 , Abhishek Joshi4 (Indian Journal of Forensic Medicine & Toxicology, 2020)
Ayurveda explains disproportion in the three doshasvata, pitta and kapha singly or all of them together cancause Apasmar. Aggravated doshas get accumulated in hridaya and create the features based upon Doshicpredominance, which cause illusion of the mind and visual hallucination and seizures (tonic spasms andclonic jerks). Often it is presented with outwarding of tongue, deviation of the eyes, dribbling of saliva withfroth, tonic and clonic movements of limbs. Epilepsy is characterized by recurrent, episodic, paroxysmal,involuntary clinical events related with alternation of cerebral function. An epileptic attack is anrapid andunwarranted electric discharge of cerebral neurons. Saraswat Churna is a popular Compound drug whichis successfully used in Psychological disorders. It is mentioned in “Unmada Prakaran” of well knownAyurvedic book of “ Bhaishgya Ratnawali” that Saraswat Churna consists of different types of MedhyaRasayana herbs like Vacha, Shankhapushpi etc. and Brahmi Swarasbhawna is given to it for three times.Phenytoin (Diphenyl Hydantoin or Dilantin) is highly effective and widely prescribed anticonvulsant drugused in the treatment of grand mal and psychomotor epilepsy. Phenytoin has been used to treat thought, moodand behaviour disorders, cardiovascular disorders, neuro muscular disorders, gastrointestinal disorders,Endocrine disorders. As Dilantin showed adverse reactions like urticarial like skin rashes, gastric irritation,resulting in nausea, vomiting, hyperplasia and hypertrophy of the gums noted in 90% of patients was notnoted in patients treated with Saraswat Churna.